Schizophrenia or frontotemporal dementia in a young Chinese female: A purview of possible diagnoses - Grewal, G.S.; Kanagasundram, S.; Jambunathan, S. (2010)
Frontotemporal dementia (FTD) is now increasingly being recognized as one of the causes of young onset dementia (YOD). The presentation of FTD can be subtle with a broad range of symptoms. This frequently causes misdiagnosis and a delay in initiating the correct treatment. While subtle personality changes, disinhibition and problems in executive functioning are frequently encountered in FTD, frank psychotic symptoms resembling schizophrenia are unusual. This is a case of a 38 yearold Chinese female that highlights how obsessive compulsive symptoms which progressed to florid psychosis and disorganized speech and behavior can be a presenting picture in FTD. For seven years, this patient was treated as a case of schizophrenia and was thought to have poor response to electroconvulsive therapy (ECT) as well as antipsychotic medication. Her blood work and electroencephalogram (EEG) were normal. Magnetic resonance imaging (MRI) showed progressive cerebral atrophy. This case report suggests that psychosis should be investigated in detail especially when the clinical presentation is not typical of a functional disorder and more so when the patient is not responsive to conventional treatment. This report also highlights the importance of eliciting symptoms suggestive of an ``organic'' etiology, such as incontinence and disorientation. In addition, the usefulness of repeated imaging to show the rapidly progressive course of FTD has been illustrated. Other possible differential diagnoses of this patient are also discussed.